Collection - Spain. Papeles Procedentes de la Isla de Cuba.
Consists of selections from selected legajos between 1 and 2375.
In part, microfilm edition only
Microfilm, photocopies and transcripts of originals in the Archivo General de Indias (Seville).
In part, positive microfilm edition produced from negative microfilm in the Library of Congress.
Archivo General de Indias
In Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room.